Faktor Penentu Keberhasilan Pembiayaan Syariah: Analisis Kepatuhan dan Pengelolaan Risiko dalam Pemberdayaan UMKM - Fawaid, Fawaid; Saini, Saini (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study analyzes the success factors of sharia financing at BMT NU Jambesari, based on the significance of sharia financing in empowering MSMEs as pillars of the Islamic economy. The study addresses gaps by emphasizing sharia compliance and risk management strategies as key elements of success. The research aims to analyze the factors that determine the success of sharia financing in empowering MSMEs. This research employs a descriptive qualitative method with data collected through interviews, observations, and documentation. The findings reveal that the success of financing relies on strong sharia compliance, adaptive risk management strategies, empowerment through training, and a community-based local approach that strengthens long-term relationships with clients.